Low-dose trimethoprim-sulfamethoxazole treatment for Pneumocystis pneumonia: a systematic review and meta-analysis - Huang, Hui-Bin; Zhu, Yi-Bing; Yu, Da-Xing (Frontiers in Pharmacology, 2024)
The recommended standard treatment for pneumocystis jirovecii pneumonia (PJP) is high-dose trimethoprim-sulfamethoxazole (TMP-SMX) (15-20 mg/kg/d TMP). However, the standard regimen may cause a high incidence of doserelated adverse events (AEs). Therefore, we aimed to conduct a systematic review and meta-analysis to evaluate the efficacy and safety of low-dose TMP-SMX regimens (<15 mg/kg/d of TMP) compared with the standard regimen in patients with PJP.We searched PubMed, Embase, and the Cochrane database for relevant articles from inception to March 10, 2024. Studies were included if they focused on PJP patients receiving a low-dose TMP-SMX regimen compared with a standard regimen.The primary outcome was mortality. We assessed study quality and performed subgroup analysis and sensitivity analysis to explore potential heterogeneity among the included studies.Results: Seven studies were included. Overall, the low-dose regimen significantly reduced the risk of mortality (odds ratio [OR]=0.49; 95% CI, 0.30-0.80; I 2 =16%; P=004). This finding was confirmed in further sensitivity and subgroup analyses. The low-dose regimen also significantly reduced total AEs (OR=0.43; 95% CI, 0.29-0.62; I 2 =0%; P<0.0001), and improved the incidence of most specific AEs (ORs ranged from 0.13-0.89). In addition, the low-dose regimen had significantly more patients completing the initial regimen (P=0.002), fewer patients requiring dose reductions (P=0.04), and almost significantly fewer patients requiring a switch to a second-line regimen (P=0.06).The limited available evidence suggests that a low-dose TMP-SMX regimen significantly reduced mortality and total AEs in PJP patients. Thus, it is one of the potentially promising therapies to PJP and more high-quality and multi-center randomized trials should be conducted in the future.